“My Brigham Baby” Application: A Pilot Study Using Technology to Enhance Parent's Experience in the Neonatal Intensive Care Unit - Erdei, Carmina; Forde, Madison; Cherkerzian, Sara; Conley, Maria S.; Liu, Cindy H.; Inder, Terrie E. (American Journal of Perinatology, 2023)
Objective This study aimed to describe the family psychosocial experience in a level-III neonatal intensive care unit (NICU), and to assess how it evolved after rollout of an educational smartphone application (App) called “My Brigham Baby.”Study Design We surveyed 25 NICU parents pre-App rollout (before coronavirus disease 2019 [COVID-19] pandemic) and 25 parents post-App rollout (during pandemic). Collected data included parental self-reported discharge readiness, symptoms of stress and anxiety, and parenting skill confidence. Survey scores were assessed as total or mean scores, and by category of severity.Results Pre-and post-App parents had comparable demographics, and their infants had similar clinical characteristics during their NICU stay. Discharge readiness differed by group status (p = 0.02) and was characterized by a greater frequency in being “very ready” for discharge among the post-App rollout parent group compared with the pre-App group (56 vs. 20%, p = 0.027), and parenting confidence shifted toward more optimal scores post-App rollout. Parental stress and anxiety symptoms did not significantly differ between groups despite possible stress contagion from the COVID-19 pandemic.Conclusion This pilot study suggests that technology Apps are feasible interventions within NICU settings and may enhance parental experiences related to NICU hospitalization.Key Points
Keywords: NICU; preterm; parent mental health; discharge readiness; technology